Leveraging Six Values for Company Performance: Adaptation of Sustainable Business Model Innovation Strategies in Chinese Electric Vehicle Brand Enterprises - Raja Nazim Bin Raja Abdullah (Tanjung Malim, 2024)
Leveraging Six Values for Company Performance: Adaptation of Sustainable Business Model Innovation Strategies in Chinese Electric Vehicle Brand Enterprises by Raja Nazim Bin Raja Abdullah